Norepinephrine dose, lactate or heart rate: what impacts prognosis in sepsis and septic shock? Results from a prospective, monocentric registry - Schupp, Tobias; Weidner, Kathrin; Rusnak, Jonas; Jawhar, Schanas; Forner, Jan; Dulatahu, Floriana; Brück, Lea Marie; Hoffmann, Ursula; Bertsch, Thomas; Akın, Ibrahim; Behnes, Michael (Current medical research and opinion, 2023)
The study comprehensively investigates the prognostic value of norepinephrine (NE) dose, lactate and heart rate in patients with sepsis and septic shock. Limited data regarding the prognostic value of NE dose, lactate and heart rate in patients meeting the sepsis-3 criteria is available. Consecutive patients with sepsis and septic shock from 2019 to 2021 were included. The prognostic value of NE dose, lactate and heart rate was tested for 30-day all-cause mortality. Statistical analyses included univariable t-tests, Spearman’s correlations, C-statistics, Kaplan-Meier analyses, as well as one-factorial repeated measures analysis of variance (ANOVA) and Cox proportional regression analyses. 339 patients with sepsis or septic shock were included. With an area under the curve (AUC) of up to 0.638 and 0.685, NE dose and lactate revealed moderate prognostic accuracy for 30-day all-cause mortality, whereas heart rate was not associated with prognosis. Very high NE doses (i.e. > 1.0 mcg/kg/min) (HR = 2.938; 95% CI 1.933 − 4.464; p = .001) and lactate levels (i.e. ≥ 4 mmol/l) (HR = 2.963; 95% CI 2.095 − 4.191; p = .001) on admission were associated with highest risk of death. Finally, increasing NE doses and lactate levels from day 1 to 3 indicated increased risk of death, which was consistent after multivariable adjustment. Both very high NE doses and lactate levels - but not heart rate - were associated with increased risk of 30-d all-cause mortality in patients with sepsis and septic shock.
Gesehen am 12.08.2024